What Will Happen to Financial Markets When the Baby Boomers Retire? - Brooks, Robin (IMF Working Papers; Working Paper ;, 2000)
This paper explores whether changes in the age distribution have significant effects on financial markets that are rational and forward-looking. It presents an overlapping generations model in which agents make a portfolio decision over stocks and bonds when saving for retirement- Using the model to simulate a baby boom-baby bust demonstrates that returns to baby boomers will be substantially below returns to earlier generations, even when markets are rational and forward-looking. This result is important because the current debate over how to reform pay-as-you-go pension systems often takes historical returns on financial assets-and on the equity premium-as given.